Democracy in Modern Iran : Islam, Culture, and Political Change. - Mirsepassi, Ali (New York : NYU Press, 2010)
Can Islamic societies embrace democracy? In Democracy in Modern Iran, Ali Mirsepassi maintains that it is possible, demonstrating that Islam is not inherently hostile to the idea of democracy. Rather, he provides new perspective on how such a political and social transformation could take place, arguing that the key to understanding the integration of Islam and democracy lies in concrete social institutions rather than pre-conceived ideas, the every day experiences rather than abstract theories. Mirsepassi, an Iranian native, provides a rare inside look into the country, offering a deep under.
Acknowledgments; Preface: "Where Is My Vote?"; Introduction: Democracy and Culture; 1 The Origins of Secularism in Europe; 2 Modern Visions of Secularism; 3 A Critical Understanding of Modernity; 4 Intellectuals and Democracy; 5 Religious Intellectuals; 6 Alireza Alavi-Tabar and Political Change; 7 The Predicaments of Iranian Public Intellectuals; 8 An Intellectual Crisis in Iran; Conclusion: Modernity and Its Traditions; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z; About the Author.
Print version record.
JSTOR
Keywords: Democracy -- Iran; Politics and culture -- Iran; Islam and politics -- Iran; Islam and secularism -- Iran; Islamic modernism -- Iran; Iran -- Politics and government; Iran -- Intellectual life; Politique et culture -- Iran; Islam et laïcité -- Iran; Modernisme islamique -- Iran; Iran -- Politique et gouvernement; POLITICAL SCIENCE -- General; Democracy; Intellectual life; Islam and politics; Islam and secularism; Islamic modernism; Politics and culture; Politics and government; Iran; Iran; Islam; Islamic; Mirsepassi; Modern; democracy; demonstrating; embrace; hostile; idea; inherently; maintains; possible; societies; that